Physical activity and health promoting lifestyle among diploma nursing students in Malaysia - Soh, Kim Geok; Soh, Kim Lam; Japar, Salimah; Ong, Swee Leong; Abdul Halain, Azura; Yusof, Aminuddin (Advanced Scientific Research, 2018)
The aims of this study are to assess the physical activity level and health-promoting lifestyle among diploma nursing students in Malaysia. Besides, this study also aims to compare whether there were significant differences in term of the physical activity level and health-promoting lifestyle between urban and rural diploma nursing students. This study involved 123 diploma nursing students who currently pursuing the diploma degrees in the two local government institutions. The YAMAX Digi-Walker pedometer was used to measure physical activity based on their weekly (7 days) step counts. And the Health-promoting Lifestyle Profile (HPLP) II questionnaire was used to measure the nursing student’s health-promoting lifestyle. The HPLP II consisted of six sub-scales which included health responsibility, physical activity, nutrition, spiritual growth, interpersonal relations, and stress management. The mean weekly step counts reported was 8839.96±2613.58 steps. The diploma nursing students in the urban institution were reported to have higher mean step counts as compare to the diploma nursing students in the rural institution. Mean score obtained for HPLP II among the diploma nursing students was 2.56±0.34. Both diploma nursing students were found to have the highest score for spiritual growth, follow by interpersonal relations and stress management. Meanwhile, health responsibility was reported to be the lowest score for both institutions. Since unhealthy behaviors are associated positively with the nurses’ health promotion roles in the future, so encouraging them to live healthily starting when they were pursuing their diploma was necessary in order to achieve this noble mission.